2023
DOI: 10.1186/s12902-023-01328-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperparathyroidism in an adolescent presenting with genu valgus progressing to extensive bone disease; a case report

Abstract: Background Primary hyperparathyroidism which is rare in adolescents presents commonly with non-specific symptoms and systemic complaints. Though there are few reported cases of genu valgus, genu valgus progressing to extensive bone disease despite mildly elevated calcium had not been reported before. Case presentation A 12-year-old male had been evaluated for bilateral (left > right) genu valgus and short stature. Serum calcium and phosphate lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…A teenager suffering from bilateral genu valgum and associated short stature was referred for orthopedic correction at the age of 15 (with normal calcium values at that point); however, 2 years later, he suffered multiple fractures due to adenoma-associated PHP causing brown tumors. A good outcome was registered after parathyroidectomy [40]. In 2020, Lee et al [39] reviewed all the cases with genu valgum and PHP reported between 1945 and 2019 and found 23 cases.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…A teenager suffering from bilateral genu valgum and associated short stature was referred for orthopedic correction at the age of 15 (with normal calcium values at that point); however, 2 years later, he suffered multiple fractures due to adenoma-associated PHP causing brown tumors. A good outcome was registered after parathyroidectomy [40]. In 2020, Lee et al [39] reviewed all the cases with genu valgum and PHP reported between 1945 and 2019 and found 23 cases.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Table 4. Case reports and series (<10 patients per article) of pediatric PHP (the list starts with the most recent publications) [9][10][11]15,29,[34][35][36][37][38][39][40]44,66,[68][69][70][71][72][73][74]77,78,[83][84][85]; the published cases with specific genetic testing were already introduced in Table 3 [17,53,61,62,64,65,67]. Abbreviations: C = case; CT = computed tomography; PT = parathyroid; PHP = primary hyperparathyroidism; SPECT/CT = single-photon emission computerized tomography/computed tomography; VATS = video-assisted thoracic surgery.…”
Section: Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…Primary hyperparathyroidism (PHPT) is a prevalent endocrine disorder marked by elevated levels of calcium in the blood and elevated or inappropriately normal levels of parathyroid hormone in the serum [5,6]. It is an infrequent condition in growing populations [7,8]. PHPT may present with osteoporosis and increased urinary calcium excretion, and it can also manifest as vertebral fractures and changes in bone structures, both of which might occur without noticeable symptoms [5].…”
Section: Introductionmentioning
confidence: 99%